2018
DOI: 10.1007/s00134-018-5218-5
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between ICU hypotension and in-hospital mortality and morbidity in septic patients

Abstract: PurposeCurrent guidelines recommend maintaining a mean arterial pressure (MAP) ≥ 65 mmHg in septic patients. However, the relationship between hypotension and major complications in septic patients remains unclear. We, therefore, evaluated associations of MAPs below various thresholds and in-hospital mortality, acute kidney injury (AKI), and myocardial injury.MethodsWe conducted a retrospective analysis using electronic health records from 110 US hospitals. We evaluated septic adults with intensive care unit (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
180
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(200 citation statements)
references
References 31 publications
11
180
2
7
Order By: Relevance
“…Third, early use of norepinephrine may improve the regional distribution of blood flow and prevent fluid overload [25]. Finally, delays in correcting hypotension are associated with increased risk of death in septic patients [33][34][35], whereby prompt correction of hypotension might influence clinical outcomes. Indeed, a recent phase II randomized controlled trial suggested that early use of norepinephrine might improve the possibility to achieve more sustained mean arterial pressure levels and adequate tissue perfusion parameters [36].…”
Section: Introductionmentioning
confidence: 99%
“…Third, early use of norepinephrine may improve the regional distribution of blood flow and prevent fluid overload [25]. Finally, delays in correcting hypotension are associated with increased risk of death in septic patients [33][34][35], whereby prompt correction of hypotension might influence clinical outcomes. Indeed, a recent phase II randomized controlled trial suggested that early use of norepinephrine might improve the possibility to achieve more sustained mean arterial pressure levels and adequate tissue perfusion parameters [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, both trials were underpowered as the mortality rate in the control groups was lower than expected. In addition, patients assigned to the low MAP target groups achieved higher MAPs than planned according to the study protocol.In a recent article in Intensive Care Medicine, Maheshwari et al report the results of a retrospective analysis of 8782 patients admitted to 110 US hospitals exploring the association between MAP and acute kidney and myocardial injury as well as in-hospital mortality in patients with septic shock [8]. Using routinely collected data from an electronic health records database, the authors defined total exposure to hypotension as the time-weighted average mean arterial pressure (TWA-MAP) and calculated the cumulative time spent below 55, 65, 75, and 85 mmHg thresholds.…”
mentioning
confidence: 99%
“…This phenomenon is called arterial hypotension and frequently occurs in Intensive Care Units (ICUs) or Operating Rooms (ORs). New researches highlight the importance of predicting hypotensive events in hospital settings by providing evidences that correlate the occurrence of intraoperative or postoperative hypotensive events and various upcoming complications [2] [3] [4] [5] [6].…”
Section: Introductionmentioning
confidence: 99%